2012
DOI: 10.4172/2157-7099.1000247
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricles of the Mature Camel Heart (Camelus dromedaries) with Special References to the Structure and Distribution of the Purkinje Cardiomyocytes:Microanatomy

Abstract: The present investigation was performed to clarify the histological features of the left ventricles in the heart of the mature dromedary camel. This investigation was carried out on the left ventricles of six healthy mature camels. Microscopically, the left ventricles is consisted of three major layers or tunics; the internal endocardium, the middle myocardium, and the external epicardium. The endocardium is consisted of three layers; the endothelial layer of simple squamous epithelium, sub-endothelial layer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Also, Kawano et al (2003) demonstrated the presence of more autonomic nerves in the subendocardial area than in the subepicardial area of the human ventricle. The intramural Purkinje fibers, in this study, were seen among the myocardium that confirms the ramification of Purkinje fibers within endocardium and myocardium as recorded by Ryu et al (2009) in sheep and Ghonimi et al (2014) in camel but, these fibers were not identified in the heart of human (Durrer et al, 1970;Oosthoek et al, 1993). The presence of intramural Purkinje fibers in the myocardium results in a more efficient excitation of the ventricles compared with the absence of intramural Purkinje fibers (Oosthoek et al, 1993;Tranum-Jensen et al, 1991) as they prevent intercyclic pre-excitation of the ventricular myocardium.…”
Section: Discussionsupporting
confidence: 81%
“…Also, Kawano et al (2003) demonstrated the presence of more autonomic nerves in the subendocardial area than in the subepicardial area of the human ventricle. The intramural Purkinje fibers, in this study, were seen among the myocardium that confirms the ramification of Purkinje fibers within endocardium and myocardium as recorded by Ryu et al (2009) in sheep and Ghonimi et al (2014) in camel but, these fibers were not identified in the heart of human (Durrer et al, 1970;Oosthoek et al, 1993). The presence of intramural Purkinje fibers in the myocardium results in a more efficient excitation of the ventricles compared with the absence of intramural Purkinje fibers (Oosthoek et al, 1993;Tranum-Jensen et al, 1991) as they prevent intercyclic pre-excitation of the ventricular myocardium.…”
Section: Discussionsupporting
confidence: 81%